Estimation of the trabecular structure of alveolar bone before implant planning in orthodontic treated patients by using fractal analysis method - Gülbahar Ustaoğlu; Duygu Göller Bulut; Burak Sarıoğlu; Handan Ankaralı; Emine Şebnem Kurşun Çakmak (Selcuk Dental Journal)
Background:The aim of this study was to assess the trabecular bone pattern changes of orthodontically treated patients before orthodontic treatment (T0), immediately after (T1) and 6 months after (T2) the treatment by using fractal dimension (FD) analysis in order to guide implant applications. Methods:Totally 32 orthodontic patients who had one missing tooth were included in the study. Patients were treated to align the teeth and to create a dimensionally appropriate space for implant placement. Panoramic radiographs were taken with standard protocols at the time periods of before (T0), immediately after (T1) and 6 months after (T2) treatment. FD analysis was performed using Image J 1.3 software with the box-counting method. Results:The highest FD value measured before treatment (T0=1.47±0.14). Mean FD values of T2 was found statistically significantly higher (1.32±0.14) than T1 (1.19±0.15) (p<0.001). Conclusions:It is suggested not to plan implant surgery immediately after the end of orthodontic treatment because trabecular bone gains more complex nature over time. FD analysis is a simple and cost-effective tool for examining bone structure in panoramic radiographs.